Foreign direct investments in the economic growth of the open economy of Ukraine - Rokocha, V.; Tkalenko, S.; Sukurova, N.; Honcharova, A.; Murashko, O.; Рокоча, Віра Володимирівна; Ткаленко, Світлана Іванівна (FINTECHALLIANCE LLC, 2021)
In terms of globalization of the world economy, the open economy of a country participating in the globalization process becomes an organic element of the world economy and thus receives additional incentives for development. International flows of goods and capital allow countries to get new sources for economic growth. Economic growth is now not only a function of internal but also of external factors. It is they who now determine the modernization tendencies of national economic policies, forcing them to move in accordance with world trends. The purpose of the research is to assess the relationship between economic growth of the country and external factors of its economic development, as well as to identify the dependency between external factors in order to clarify their role in the modernization of national economy. With this aim, the analysis of the main parameters of openness of Ukraine’s economy is carried out, as of external factors that influence on the national economic development, changes in the traditional production function under the influence of introduction in it of external factors of development, the estimated indicators of the named influences are modeled. The novelty of the research is the identification of dependency between the forms of openness of the economy and economic growth, the development of a model of relationship between the forms of openness of the economy. Research method. The study is based on a set of economic and economic-mathematical methods that are needed to identify the influence of external factors on the national economy, especially methods of abstraction, systematic and structural-comparative analysis, synthesis and modeling of economic processes. Among the models used in the research is a multifactor regression model. The empirical basis was the materials of official statistics of Ukraine for 1999—2019. The results of research showed: the role of globalization of Ukraine’s economy in its economic development, the importance of FDI as an external factor of economic development, the strong link between international capital flows and international flows of goods into the Ukrainian economy, the positive impact of the latter on the former.
Keywords: economic growth globalization, external factors of economic growth, production function, open economy, FDI, foreign trade, government investment policy.; economic growth; globalization; external factors of economic growth; production function; open economy; FDI; foreign trade; government investment policy